2020
DOI: 10.3389/fimmu.2020.608645
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Type I and III Interferons at Respiratory and Intestinal Barrier Surfaces

Abstract: Interferons (IFNs) constitute the first line of defense against microbial infections particularly against viruses. They provide antiviral properties to cells by inducing the expression of hundreds of genes known as interferon-stimulated genes (ISGs). The two most important IFNs that can be produced by virtually all cells in the body during intrinsic innate immune response belong to two distinct families: the type I and type III IFNs. The type I IFN receptor is ubiquitously expressed whereas the type III IFN re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 123 publications
(195 reference statements)
1
108
1
3
Order By: Relevance
“…For example, the host response to viral infection is dependent on the expression kinetics of type I and III IFNs, among others. The expression of IFNβ and IFNλ mRNA peaked at 16 and 24 hpi, respectively, in intestinal enteroids infected with reovirus [41], consistent with the notion that type III IFN responses are generally of lower magnitude, slower kinetics and longer duration compared to type I IFN responses [46]. Thus, sampling of the IFN Informed Consent Statement: Not applicable.…”
Section: Discussionsupporting
confidence: 69%
“…For example, the host response to viral infection is dependent on the expression kinetics of type I and III IFNs, among others. The expression of IFNβ and IFNλ mRNA peaked at 16 and 24 hpi, respectively, in intestinal enteroids infected with reovirus [41], consistent with the notion that type III IFN responses are generally of lower magnitude, slower kinetics and longer duration compared to type I IFN responses [46]. Thus, sampling of the IFN Informed Consent Statement: Not applicable.…”
Section: Discussionsupporting
confidence: 69%
“…The relationship between IFN-λs and epithelial barrier protection in various organs, e.g. respiratory tract, lungs, and gastrointestinal tract had been well-established ( Lozhkov et al, 2020 ; Stanifer et al, 2020 ). The ex vivo infection model showed that the barrier gene FLG and IVL were generally inhibited in S. aureus infection model.…”
Section: Discussionmentioning
confidence: 99%
“…They need to act tolerogenic to the vast amount of bacterial commensals but at the same time also be responsive to detrimental pathogens. In this context, there is increasing evidence that both type I and type III IFNs are important for the maintenance of the intestinal epithelial barrier integrity and the control of adaptive immune responses including antiviral responses ( 81 , 82 ). In the intestine, type I IFNs are for example continuously produced by CD11c + DCs of the lamina propria ( 83 ).…”
Section: Role Of Ifns In the Murine And Human Intestinementioning
confidence: 99%